Die kaiserliche Gemäldegalerie und die Anfänge des öffentlichen Kunstmuseums, Band 1 Die Kaiserliche Galerie im Wiener Belvedere (1776-1837) - Swoboda, Gudrun (2014)
The publication focuses on the - for Europe - radical and influential new installation of the Imperial Picture Gallery in Vienna at the turn of the 19th century, a seminal time of change both for art-history and European civilization. Function, internal structure and presentation of the Imperial Picture Gallery evolved in a way that was to prove exemplary: the princely gallery was transformed into a public art museum, with a new installation at Belvedere Palace that reflected art-historical principles.